Does on-the-job training help graduates find a job? Evidence from an Italian region - Corinna Ghirelli; Enkelejda Havari; Giulia Santangelo; Marta Scettri (Publications Office of the European Union, 2018)
This paper provides an evaluation of a training programme for graduates entitled "Work Experience for Graduates" (WELL - Work Experience Laureati and Laureate) that was recently implemented in Italy. The aim of the programme was to increase the career prospects of unemployed graduates in the region of Umbria. It consisted of two measures: (i) on-the-job training for unemployed graduates, and (ii) wage subsidies to firms and organisations for hiring the trainees at the end of the programme. We rely on administrative data and match- ing methods to evaluate the effectiveness of the intervention in terms of the employability of participants. Results indicate that WELL participants are more likely to be employed and to sign an apprenticeship contract within the region. We also find substantial gender differences in employability and the type of contract obtained, with men having a higher probability of finding a job (permanent contract or apprenticeship). We show that this may be explained by different choices in terms of field of study, with males being more prone to enrolling in scientific areas and females in the humanities.
Keywords: I0; J0; D04; J48; 330; training; graduates; matching; propensity score; policy evaluation; Italy